Legal Protection for Children Using Paracetamol Syrup Products from the Perspective of Maslahah (A Case Study of Atypical Progressive Acute Kidney Injury) - Handayani, Fitri; Wiyono, Wiwin Muchtar; Erowati, Eti Mul; Purwendah, Elly Kristiani (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2025)
This study examines the legal accountability and consumer protection frameworks in Indonesia concerning the widespread health crisis caused by the consumption of contaminated paracetamol syrup, which led to cases of Atypical Progressive Acute Kidney Injury (AKI) in children. Using a normative juridical method, the research analyzes relevant statutory regulations, such as Law No. 8 of 1999 on Consumer Protection and Law No. 36 of 2009 on Health, alongside Islamic legal principles, particularly maslahah (public interest). The discussion focuses on the obligations of pharmaceutical companies and the regulatory role of the Indonesian Food and Drug Authority (BPOM) in ensuring the safety and quality of pharmaceutical products. Findings reveal that both the manufacturers and BPOM failed to fulfill their legal duties, leading to significant material and immaterial losses for affected consumers. From an Islamic legal perspective, the concept of maslahah underscores the moral and legal imperative to protect life and public welfare, supporting the need for stricter enforcement and accountability. The study concludes that a more robust legal and ethical framework is essential to protect children as vulnerable consumers, and it advocates for an integration of national law and Islamic principles to ensure justice, transparency, and the prevention of similar incidents in the future.